(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
This study aimed to identify the extent of the availability of soft skills in the performance of faculty members in Saudi universities from their point of view by applying it to faculty members at Imam Muhammad bin Saud Islamic University and Shaqra University, and to rank the soft skills according to the degree of their importance to them and whether there are statistically significant differences when The level of significance (a=0.05) in the degree of availability of soft skills in their performance is due to the variable of years of teaching or college experience. The study followed the descriptive approach to achieve its objectives, as the researcher used the questionnaire as the main tool for the study, which contained (43) items distributed over six axes: critical thinking skill, problem solving, time management skill, leadership skill, decision-making skill, teamwork skill, and communication skill The study concluded that soft skills were highly available in the performance of faculty members at Imam and Share Universities, as the highest arithmetic average for a sub-skill reached (4.85), with a rate of (97%), with a very high degree of availability, while the average for the lowest sub-skill reached (3.61), with a rate of (71%). With a high degree of availability. The skill of communication and communication came in first place in terms of its importance with an arithmetic average of (4.42), with a percentage of (88.2%) and a very high degree of availability. It was followed by the teamwork skill in second place with an arithmetic average of (4.28), with a percentage of (86%) and a degree of availability. Very high, while the time management skill came in third place with an arithmetic average of (4.18), with a percentage of (83.5%) and a high degree of availability, and in fourth place came the leadership skill with an arithmetic average of (4.12), with a percentage of (80.1%) and a high degree of availability. The skill of critical thinking and problem solving came in fifth place with an arithmetical average of (4.04), with a percentage of (80.1%) and a high degree of availability, while the decision-making skill came in last place with an arithmetical average of (4.03), with a percentage of (80%) and a high degree of availability.